An Abrasion, a Prosthetic Shoulder, and a Cat with a Licking Tendency: Case Report and Literature Review of P. multocida Joint Seeding. (18th November 2020) - Abel, William F.; Eckman, Christopher S.; Summers, Robert P.; Sessions, William S.; Schnee, Amanda E.
Abstract : Pasteurella multocida is a pathogen well known for its zoonotic transmission, most commonly by cats and dogs. When bacteremia ensures from an infection, patients with foreign objects present in their bodies, including prosthetic joints and mesh implants, become vulnerable to seeding. There have been multiple documented cases in which P. multocida bacteremia has resulted in infection of both native and prosthetic joints. Furthermore, cases have been documented in which patients with P. multocida bacteremia have developed meningitis and neurological complications. Here, we present a patient with multiple comorbidities including multifactorial immunocompromise, advanced age, and multiple prosthetic joints who developed prosthetic joint infection and spinal osteomyelitis after the development of Pasteurella bacteremia. Aggressive treatment was undertaken given her risk factors, and a combination of antibiotics and surgery was utilized, with the patient making a full recovery.